If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(2a + -5) = 12 Reorder the terms: 6 + -2(-5 + 2a) = 12 6 + (-5 * -2 + 2a * -2) = 12 6 + (10 + -4a) = 12 Combine like terms: 6 + 10 = 16 16 + -4a = 12 Solving 16 + -4a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -4a = 12 + -16 Combine like terms: 16 + -16 = 0 0 + -4a = 12 + -16 -4a = 12 + -16 Combine like terms: 12 + -16 = -4 -4a = -4 Divide each side by '-4'. a = 1 Simplifying a = 1
| x*.2=295 | | 6y-21=y-21 | | 5/6•3/10 | | (x-18)+8x=180 | | X^5+2x^3+x-1=3 | | 5=15-5a | | X^5+2x^3+x-4=0 | | 6/7x+1/2=7/8 | | 7-3w=2 | | 9=4-c | | 3=9b+12 | | 4+x/58 | | 5a+7-3a-2=2 | | 4+×/5=8 | | 2y-5x=-10 | | n*0.5=-13 | | x+.03x=y | | 7x-7(x+6)=10 | | x^2-xy+y^2=39 | | 4x^2-18=-x | | 3/2x-1/x-1=2/3x^2+3x | | 3(1+2y)+7y=19 | | (-3*x+5)/(5-x^2)=11 | | 2.5x+-5/2x+12=12 | | 2.5x+-5/2x | | x+1=72/x | | 2(x-1)+3+-2x=7 | | showthat:sin(pi/4+4x)=sin(pi/3-2x) | | 1.00+3.00=3.00+2.00 | | x=r+4+4r-2 | | 2y-8=5x | | M^2-11=38 |